Bond length variations: electron number profiles and transferable atomic sizes - Ganguly, Parthasarathy; Kulkarni, Bhakti S.; Pal, Sourav (Journal of Molecular Structure, 2009)
A profile of the number of electrons with distance along the M-X bond in gas-phase diatomic molecules has been obtained from electron density plots calculated using DFT B3LYP 6-311G** method for some representative molecules. This ``number profile'' is compared with that expected from the partitioning of the 1D bond-distance into atom-specific transferable ``hub'' or core atomic sizes of the M and X atoms and another ``axle'' size which is associated with a pair of (bonding) electrons. The ``hub'' size is proportional to a core atom-specific size, r(nZ)(c) with r(nZ)(c)(M) >= r(nZ)(c)(X). For ``single bonds'', the ``hub'' size for M atom is C(M)r(nZ)(c)(M) and for X atom is C(X)r(nZ)(c)(X). The ``axle'' size, DMX, is usually the ordinary (similar to 4a(H)/3 where a(H) is the Bohr radius of the hydrogen atom) or elongated (similar to 2a(H)) bond length of the hydrogen molecule. The ``hub'' and ``axle'' sizes could be characterized ``charge-transfer'' (C(M) = pi(2/3) = 2.144; C(X) = pi(4/3)/2 = 2.300 and D(MX) = 4a(H)/3) or ``neutral'' (CM or C(X) = 1, 2, ... and D(MX) = 2a(H)). We use a new ``static'' or ``peripatetic'' classification for the core sizes which is derived from a new condition for metallization in elements based on atomic size. The charge-transfer distance, d(MX)(+/-), is usually found for ``static'' conditions while the ``neutral'' description is usually found when X = F or for ``peripatetic'' conditions. Such a partitioning is seen to agree with that from the plot of the total number of electrons, N(el), vs r along a bond axis. The Nel vs r plots from each atom are described by a simple hydrogen-atom-like function which differ away (''out'') or towards (''in'') the M-X bond. Thus N(in,out)(M, X) = (Z(M,X) +/- 1) exp (-r/B(in,out)) where the minus sign is associated with M and plus sign with X and Bin, out being related inversely to the Slater orbital exponent. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: B3LYP; Bond length; Bond-stretch isomer; DFT; Diatomic molecule

Behaviour of density functional theory for electric response properties at distorted geometries of molecules - Shedge, Sapana V.; Joshi, Sayali P.; Pal, Sourav (Theoretical Chemistry Accounts, 2012)
The role of exchange-correlation is well known for accurate calculations of electric response properties. The exchange-correlation functional in density functional theory (DFT) has been well studied for ground state equilibrium geometry. However, the behaviour of these functional in stretched geometries, where static correlation play an important role, has not been studied systematically, particularly for response electric properties. Thus, we present here the rigorous calculation of electric response properties at distorted geometries of the molecules. We have considered dipole polarizability and dipole-quadrupole polarizability for description of role of static and dynamic correlation for electric response properties. The calculations are performed with our new approach, noniterative approximation to coupled-perturbed Kohn-Sham method. These DFT results are compared with higher level ab initio such as coupled perturbed singles and doubles and fully correlated full CI. We have studied single, double and triple-bonded systems at different inter-nuclear separation. We report here the dipole polarizability and dipole-quadrupole polarizability of HF, BH, H2CO, CO and NO+. We also present the effect of basis and functional on polarizability and dipole-quadrupole polarizability.
Keywords: DFT; Dipole-dipole polarizability; Dipole-quadrupole polarizability; Distorted geometry; NIA-CPKS